Inhibition of AURKA kinase activity suppresses collective invasion in a microfluidic cell culture platform - Jiang-Long Xia (Nature Portfolio, 2017)
Abstract Tumor local invasion is the first step of metastasis cascade which remains the key obstacle for cancer therapy. Collective cell migration plays a critical role in tumor invading into surrounding tissues. In vitro assays fail to assess collective invasion in a real time manner. Herein we aim to develop a three-dimensional (3D) microfluidic cell invasion model to determine the dynamic process. In this model, collective invasion of breast cancer cells is induced by the concentration gradient of fetal bovine serum. We find that breast cancer cells adopt a collective movement rather than a random manner when the cells invade into extracellular matrix. The leading cells in the collective movement exhibit an increased expression of an Aurora kinase family protein - AURKA compared with the follower cells. Inhibition of AURKA kinase activity by VX680 or AKI603 significantly reduces the phosphorylation of ERK1/2 (Thr202/Tyr204) and collective cohort formation. Together, our study illustrates that AURKA acts as a potential therapeutic target for suppressing the process of tumor collective invasion. The 3D microfluidic cell invasion model is a reliable, measurable and dynamic platform for exploring potential drugs to inhibit tumor collective invasion.